2013
DOI: 10.1371/journal.pone.0083474
|View full text |Cite|
|
Sign up to set email alerts
|

Low Levels of Peripheral CD161++CD8+ Mucosal Associated Invariant T (MAIT) Cells Are Found in HIV and HIV/TB Co-Infection

Abstract: BackgroundHigh expression of CD161 on CD8+ T cells is associated with a population of cells thought to play a role in mucosal immunity. We wished to investigate this subset in an HIV and Mycobacterium tuberculosis (MTB) endemic African setting.MethodsA flow cytometric approach was used to assess the frequency and phenotype of CD161++CD8+ T cells. 80 individuals were recruited for cross-sectional analysis: controls (n = 13), latent MTB infection (LTBI) only (n = 14), pulmonary tuberculosis (TB) only (n = 9), HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
107
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(131 citation statements)
references
References 31 publications
22
107
2
Order By: Relevance
“…The frequency of MAITs is also modified in nonbacterial diseases: increased in recently diagnosed multiple sclerosis patients (12,13), but decreased in obesity, type-2 diabetes (14), inflammatory bowel disease (15), and HIV (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of MAITs is also modified in nonbacterial diseases: increased in recently diagnosed multiple sclerosis patients (12,13), but decreased in obesity, type-2 diabetes (14), inflammatory bowel disease (15), and HIV (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…CD8 + CCR6 + mucosal-associated invariant T cells in infected HIV patients tend to have lower surface CCR6 expression compared with healthy control mucosalassociated invariant T cells [56,57], possibly leading to their failure to migrate to key immunological sites.…”
Section: T H 17-like Cells and Precursorsmentioning
confidence: 99%
“…10,[16][17][18][19] MAIT cell activation can result from either TCR-dependent signalling (triggered by ligand presented on MR1 by antigen-presenting cells) or from TCR-independent cytokine signalling. [20][21][22][23] Like other 'innate-like' lymphocytes including invariant natural killer T ª 2016 John Wiley & Sons Ltd, Immunology, 150, [45][46][47][48][49][50][51][52][53][54] cells and natural killer cells, MAIT cells respond rapidly to activation by producing cytokines and cytolytic products. Upon TCR-dependent or TCR-independent activation, MAIT cells produce interferon-c (IFN-c), tumour necrosis factor-a (TNF-a), cytolytic products (perforin, granulysin and granzymes) and degranulate (exposing CD107a to the cell surface).…”
Section: What Are Mait Cells and What Is Known About Their Phenotypementioning
confidence: 99%
“…21 Recently, however, a report by van Wilgenburg et al 48 has demonstrated that MAIT cells can be activated in an MR1-independent cytokine-driven manner by dengue virus, hepatitis C virus and influenza virus. Interleukin-18 signalling is most central to MAIT activation in these settings, though the effects of other virally driven cytokines [49][50][51][52][53][54] Interestingly, the degree of MAIT cell depletion does not correlate to the usual markers of HIV disease progression, including the degree of peripheral CD4 + T-cell depletion or the level of viral replication in the blood (HIV viral load). 51,54 Even individuals who appear to have a natural ability to control HIV infection (long-term non-progressors and elite controllers) have been found to experience similar levels of MAIT cell depletion to those observed in people with chronic progressive HIV infection.…”
Section: Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation